2015
DOI: 10.1051/0004-6361/201526427
|View full text |Cite
|
Sign up to set email alerts
|

TRAPPIST photometry and imaging monitoring of comet C/2013 R1 (Lovejoy): Implications for the origin of daughter species

Abstract: We report the results of the narrow-band photometry and imaging monitoring of comet C/2013 R1 (Lovejoy) with the robotic telescope TRAPPIST (La Silla observatory). We gathered around 400 images over 8 months pre-and post-perihelion between September 12, 2013 and July 6, 2014. We followed the evolution of the OH, NH, CN, C 3 , and C 2 production rates computed with the Haser model, as well as the evolution of the dust production. All five gas species display an asymmetry about perihelion, since the rate of brig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…With our lower bound of Q(C 2 ) ≈ 5.1×10 23 s −1 , and the upper limit adopted from Kareta et al (2019), we find a bound on the slope γ < −10.6. This slope is significantly steeper than those of other comets in our Solar System, such as γ = −3.56 ± 0.16 for C/2013 R1 (Lovejoy) (Opitom et al 2015), γ = −4.10 ± 0.10 for 103P/Hartley 2 (Knight & Schleicher 2013), and γ = −2.60 to −4.39 for 81P/Wild 2 (Lin et al 2012). The steeper slope for 2I/Borisov suggests that its C 2 production rate might be more sensitive to the heliocentric distance r h than the Solar System comets.…”
Section: Discussionmentioning
confidence: 57%
“…With our lower bound of Q(C 2 ) ≈ 5.1×10 23 s −1 , and the upper limit adopted from Kareta et al (2019), we find a bound on the slope γ < −10.6. This slope is significantly steeper than those of other comets in our Solar System, such as γ = −3.56 ± 0.16 for C/2013 R1 (Lovejoy) (Opitom et al 2015), γ = −4.10 ± 0.10 for 103P/Hartley 2 (Knight & Schleicher 2013), and γ = −2.60 to −4.39 for 81P/Wild 2 (Lin et al 2012). The steeper slope for 2I/Borisov suggests that its C 2 production rate might be more sensitive to the heliocentric distance r h than the Solar System comets.…”
Section: Discussionmentioning
confidence: 57%
“…On the other hand, water production rates determined from water IR emissions with NIRSPEC at the Keck Observatory by Paganini et al (2014) over the pre-perihelion heliocentric distance range from 1.35 to 1.16 AU are systematically a factor of 2 or more below the SWAN values and the one overlapping value from . Similarly the ground-based nearultraviolet OH production rates given by Opitom et al (2015), after accounting for the ~0.82 OH yield from H 2 O photodissociation (Combi et al, 2004), like the NIRSPEC/Keck observations given by Paganini et al (2014), are systematically smaller by factors of 2 or more from the SWAN and IRAM rates. Figure 4b also shows various water production rate measures for comet C/2013 R1 (Lovejoy) determined from different observations.…”
Section: Results Of Model Analyses For Each Cometmentioning
confidence: 82%
“…Figure 4b also shows various water production rate measures for comet C/2013 R1 (Lovejoy) determined from different observations. Opitom et al (2015) have adopted the OH Haser scale lengths and methods from A' Hearn et al (1995) to calculate OH production rates. Schleicher and Osip (2002) has shown that in order to compare water production determined from OH observations with those of other methods that the production rates need to be corrected for the more appropriate vectorial model (Festou, 1981), which is more typically used by spacebased ultraviolet observations of OH (e.g., Swift by Bodewits et al, 2014).…”
Section: Results Of Model Analyses For Each Cometmentioning
confidence: 99%
See 1 more Smart Citation
“…Used with the 2 × 2 binning mode it results in a pixel scale of 1.3 arcsec and a field of view of 22 arcmin. The observations of comet 67P have been performed once or twice a week in 2016 with a JohnsonCousins Rc filter and with exposure times ranging from 180 to 240 s. TRAPPIST images are reduced following a standard procedure described in Opitom et al (2015). The sky background is subtracted and the photometric calibration is performed using regular observations of photometric standard stars.…”
Section: Ground-based Observationsmentioning
confidence: 99%